Clinical and Radiological Management and Outcome of Pregnancies Complicated by Cerebral Venous Thrombosis: A Review of 19 Cases - Demir, Caner Feyzi; Inci, Mehmet Fatih; Ozkan, Fuat; Yildiz, Mustafa; Ozdemir, Hasan (Elsevier Science Bv, 2013)
Background: We sought to determine the risk factors and clinical outcomes of pregnant women with cerebral venous thrombosis (CVT). Methods: Nineteen pregnant patients with a diagnosis of CVT were followed in the neurology unit between 2009 and 2012. Patients with central nervous system infection and with CVT secondary to invasive procedures were excluded. Magnetic resonance imaging and magnetic resonance venography were performed for all patients. Results: There were 19 pregnant women ranging in age from 18 to 38 years (mean 27.5 years). The follow-up period ranged from 11 to 24 months (mean 19 months). Symptoms and signs that suggested a rise in intracranial pressure were present nearly in all cases, including headache, vomiting with or without nausea, disturbances of consciousness, and papilledema. Seizures and status epilepticus (with or without preeclampsia) were present in 8 cases. The rate of CVT was higher in the third trimester. The superior sagittal and transverse sinuses were the most commonly affected cerebral sinuses in our patients, and parenchymal involvement was present in 7 patients. There was no maternal mortality, and 20 infants were still alive and healthy. Conclusions: If magnetic resonance imaging is available, it should be used for the detection of CVT in all pregnant patients instead of computed tomography. Patients with parenchymal lesions, thrombophilia, and antiphospholipid syndrome had a greater risk of being left with neurologic sequelae. For pregnant patients with CVT, low molecular weight heparin in full anticoagulant doses should be continued throughout the pregnancy. Anticoagulant therapy did not appear to predispose patients to further intracranial hemorrhage.
Keywords: Cerebral venous thrombosis; pregnancy; magnetic resonance venography